Considering Historical (Dis) Continuities of Media (Literacy) Education in the Czech Republic for the Future Approach - Sloboda, Zdeněk (Communication Today, 2018)
Nowadays mediatised society, with significant grow of popularity of so-called new media, calls for a new or at least innovated media (literacy) education. In this study I challenge this assumption and critically approach the current state. In my text, I review the current discussion in the Czech Republic, as well as historical mediaeducational moments, which I consider crucial and exemplary in order to showcase the fragmentation of the whole field. I point out the elementary educational principles and their more or less explicit inclusion of media, as already formulated by Comenius in the 17th century. Further in the text I focus on the didactical use of film at schools and the aesthetically framed film education of both the 1960s and 2010 (when it was introduced to the school curricula). This leads me to a critical analysis of the curricular Media Education as it has been introduced to the whole Czech system of formal education since 2006. By discussing these three fragments, I create a momentum of continuity within the field; a continuity that provides a rich body of theoretical framing(s), terminological and practical experience and tools. This enables me to advocate for an integrated, historically rooted approach to media (literacy) education which will be not only suitable for the current situation of traditional and new media, but will also be capable to adjust educational actions with less effort and less fragmentation to the future development of media.